2004
DOI: 10.1080/00365540410019264
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Seoul Hantavirus in Rattus norvegicus in Indonesia

Abstract: The first genetic evidence for the presence of Seoul hantavirus (SEOV) in Indonesia is presented. Partial M segment sequence was recovered from the lung tissue of Rattus norvegicus trapped in central Jakarta. The sequence belongs to SEOV genotype and is most closely related to the strain B-1 from Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
35
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 11 publications
1
35
0
3
Order By: Relevance
“…The clinical symptoms were mainly consistent with mild forms of HFRS but exact type(s) of the hantaviruses involved remained unknown at that time. Later, the first confirmation of human SEOV infection was obtained (see Plyusnina et al, 2004). In this study, we continued our analyses of hantavirus-infected rodents and found a novel hantavirus in Asian house rats R. tanezumi.…”
supporting
confidence: 55%
See 3 more Smart Citations
“…The clinical symptoms were mainly consistent with mild forms of HFRS but exact type(s) of the hantaviruses involved remained unknown at that time. Later, the first confirmation of human SEOV infection was obtained (see Plyusnina et al, 2004). In this study, we continued our analyses of hantavirus-infected rodents and found a novel hantavirus in Asian house rats R. tanezumi.…”
supporting
confidence: 55%
“…These two sibling species can be differentiated, e.g. by chromosomal or electrophoretic protein analysis] and Rattus exulans in several provinces (Ibrahim et al, 1996;Plyusnina et al, 2004). The Seoul virus (SEOV) genome sequence was recovered from R. norvegicus captured in Jakarta (Plyusnina et al, 2004).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In other East Asian countries, such as Thailand, Indonesia, Vietnam, Sri Lanka and India, prevalence of SEOV and THAIV infection has been shown among rodents and humans [2,3,6,13,14,16,17,22].…”
mentioning
confidence: 99%